Multi-omics insights into the mechanisms of muscle damage induced by molybdenum exposure in goats - Xinhong Zhou; Xiaoyun Shen (Ecotoxicology and Environmental Safety)
Molybdenum (Mo) is an essential trace element, yet excessive intake can result in toxicity, adversely affecting animal health and food safety. Due to increasing environmental Mo contamination from industrial and agricultural activities, understanding its toxic effects on livestock is of global concern. This study aimed to investigate the molecular mechanisms of Mo-induced muscle damage in goats using an integrative multi-omics approach. Twenty black goats were divided into a control group (CJM) and a Mo-exposed group (JM; 50 mg/kg Na2MoO4·2 H2O), and fed for 60 days. Compared with the CJM group, the JM group showed significantly reduced muscle fiber diameter, average cross-sectional area, and levels of sulfur, iron, copper, and zinc, along with significantly increased Mo accumulation (p < 0.05). Compared with the CJM group, the JM group showed significantly reduced cysteine, methionine, proline, glutamate, and arginine (p < 0.05). Metabolomics identified 274 significantly altered metabolites, primarily enriched in energy and amino acid metabolic pathways. Proteomics revealed 221 differentially expressed proteins related to stress response, protein synthesis, and energy metabolism. These proteins interfere with muscle development by affecting cell stress responses, protein synthesis, and energy metabolism pathways. Moreover, the protein digestion and absorption and sulfur metabolism pathways were significantly associated with both metabolomics and proteomics. We found that Mo exposure primarily affects muscle energy and amino acid metabolism, thereby impairing muscle development in goats. This is the first study to use multi-omics integration to elucidate the mechanism of Mo-induced muscle toxicity in goats, providing new insights into heavy metal toxicity and food safety risks in livestock.